Analysis of factors for the development of childhood obesity as a measure for its prevention (Research, Society and Development, 2024)
Objective: To present the main causes of the development of childhood obesity and ways to mitigate the growth of this disease. Method: An integrative literature review was carried out in March 2024, using the descriptors “Indicators of Quality of Life”, “Pediatric Obesity” and “Risk”, through the PubMed and VHL databases. Results and Discussions: Some conditions are intrinsically related to the development of childhood obesity, such as behavioral, environmental, biological and genetic factors. Among these, the practice of inadequate eating habits was seen as the most influential factor in the occurrence of this disease. Furthermore, a trial called ToyBox showed that sedentary habits, such as watching television and playing electronic games, encourage the consumption of high-calorie foods. Others have observed that there has been a decline in physical fitness levels in children and adolescents around the world, and that this condition is directly proportional to the increase in metabolic risk in this age group. Finally, relating the dimensions of sleep and the risk of childhood overweight or obesity, it was shown that poor sleep habits from the age of 1 increase the risk of developing obesity in the long term. Final Considerations: Therefore, childhood obesity is a disease that can cause numerous chronic and serious problems not only during childhood but also during adult life. The development of this condition is related to factors that can be modified.